Expression and Secretion of CXCL-8 and CXCL-10 From <emph>Mycobacterium Bovis</emph> BCG-Infected Human Epithelial Cells: Role of IL-4 (Hindawi Limited, 2006)
CXC chemokine release can be modulated by Th2-derived cytokines. Interleukin(IL)-4 is one of the cytokines that are the hallmark of the Th-2 response, and plays an important role in human tuberculosis. In the current study, we investigated the effect of IL-4 on chemokine production by human epithelial cells infected with <emph>Mycobacterium bovis</emph> bacillus calmette-guérin (BCG). Gene expression of CXCL-8 and CXCL-10 was determined by the reverse transcription (RT)-polymerase chain reaction method. The levels of immunoreactive CXCL-8 and CXCL-10 were determined by enzyme-linked immunosorbent assay. We found that, although <emph>M. bovis</emph> BCG induced gene expression of CXCL-8 and CXCL-10 in <emph>M. bovis</emph> BCG-infected human epithelial cells, CXCL-8 mRNA level was significantly reduced by IL-4, whereas no significant effect of IL-4 was observed on CXCL10 mRNA level. In addition, IL-4 decreased CXCL-8 (in a graded and significant manner) but not CXCL-10 secretion. These results were further confirmed, since a significant reversion was obtained with a neutralizing antibody to human IL-4, whereas an isotype-matched control antibody had no significant effect on CXCL-8 secretion. Furthermore, we found a similar effect of IL-4 on <emph>M. bovis</emph> BCG-induced CXCL-8 and CXCL-10 secretion by using other human epithelial A549 cell line. Collectively, these data demonstrate that <emph>M. bovis</emph> BCG-infected human epithelial cells can have an active role in a local inflammatory immune response via the secretion of CXC chemokines which can be selectively regulated by Th2-derived cytokines.